1981
DOI: 10.1346/ccmn.1981.0290206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SiO2/Al2O3 Ratio on the Thermal Reactions of Allophane. II. Infrared and X-Ray Powder Diffraction Data

Abstract: Abstract--Allophanes with SiOJAI203 molar ratios from 1.38 to 1.92 were heated at temperatures up to 500~ and the changes induced were investigated by means of infrared spectroscopy (IR) and X-ray powder diffraction (XRD). Heat treatment caused the IR absorption band near 1000 cm -1 due to Si-O stretching to shift towards higher frequencies, and the band near 450 cm -1 due to O-Si-O bending to increase markedly in intensity. These results are probably due to condensation of SiO tetrahedra, following breakdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…The position of the first band did not change, but its intensity was increased by heating and attained its m a x i m u m at 400 ~ to 500~ suggesting that the dehydroxylated allophane still consisted of spherical particles similar to those found in unheated allophane. This finding is surprising because Henmi and Wada (1976) found that the "hollow" allophane spherical particles broke down very easily in the electron beam, and other workers found that heating caused substantial changes on the infrared spectra of allophane (Kitagawa, 1974;Egashira and Aomine, 1974;Henmi et al, 1981). As illustrated in Figure 4 for the Ki-P sample, however, electron microscopy confirmed that allophane heated at 500~ still consisted of the spherical particles with diameters of 35 to 40 A.…”
Section: Allophanementioning
confidence: 98%
“…The position of the first band did not change, but its intensity was increased by heating and attained its m a x i m u m at 400 ~ to 500~ suggesting that the dehydroxylated allophane still consisted of spherical particles similar to those found in unheated allophane. This finding is surprising because Henmi and Wada (1976) found that the "hollow" allophane spherical particles broke down very easily in the electron beam, and other workers found that heating caused substantial changes on the infrared spectra of allophane (Kitagawa, 1974;Egashira and Aomine, 1974;Henmi et al, 1981). As illustrated in Figure 4 for the Ki-P sample, however, electron microscopy confirmed that allophane heated at 500~ still consisted of the spherical particles with diameters of 35 to 40 A.…”
Section: Allophanementioning
confidence: 98%
“…The Egmont sample (Eg) contains "proto-imogolite" allophane and Copyright 9 1984, The Clay Minerals Societyis comparable with sample 923. The properties of the Te Akatea (Te Ak) and Kakino (KnP) allophanes were reported by Perrott (1977) and Henmi et al (1981), respectively. The clays (< 2 #m) were isolated by centrifugation after overnight mechanical dispersion in distilled water, and used without further chemical pretreatment.…”
Section: Samplesmentioning
confidence: 99%
“…4.6 <2-~tm fraction, from Kuzuu mine, Tochigi, Japail. Henmi et al (1981) Henmi et al (1983 Hayashi (1963) Oinuma and Hayashi (1968) Sakamoto and Sudo (1958) Imai et al (1969) studied in a basic tiron solution. To explain these dissolution behaviors, a mass-balance equation of the specified cation in liquid phases has been proposed.…”
Section: Introductionmentioning
confidence: 99%